2019
DOI: 10.1093/infdis/jiz303
|View full text |Cite
|
Sign up to set email alerts
|

Improving Case-Based Meningitis Surveillance in 5 Countries in the Meningitis Belt of Sub-Saharan Africa, 2015–2017

Abstract: Background The MenAfriNet consortium was established in 2014 to support implementation of case-based meningitis surveillance in 5 countries in the meningitis belt of sub-Saharan Africa: Burkina Faso, Chad, Mali, Niger, and Togo. Assessing surveillance performance is critical for interpretation of the collected data and implementation of future surveillance-strengthening initiatives. Methods Detailed epidemiologic and laborato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 16 publications
0
19
0
Order By: Relevance
“…Average CFRs in our review were within the range of those found in NmA epidemics in the region, which oscillated around 10% [23] and were as low as 4% in the Nigeria 2009 outbreak [24]. It should be noted that ascertainment of meningitis deaths, and therefore estimation of CFR, is often variable and dependent on a country’s surveillance system and performance [25].…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Average CFRs in our review were within the range of those found in NmA epidemics in the region, which oscillated around 10% [23] and were as low as 4% in the Nigeria 2009 outbreak [24]. It should be noted that ascertainment of meningitis deaths, and therefore estimation of CFR, is often variable and dependent on a country’s surveillance system and performance [25].…”
Section: Discussionmentioning
confidence: 68%
“…The population-based ES, currently covering all districts from 24 countries in the region, produces reliable, essential data for decision making during outbreak response [2]. Maintenance and strengthening of ES in all countries of the belt is recommended, accompanied by strong laboratory capacity [25].…”
Section: Discussionmentioning
confidence: 99%
“…We also reaffirmed the predominance of serotype 1 in pneumococcal meningitis clusters and outbreaks [8] , [43] . Though we did not retrospectively identify any clear cases where reactive vaccination with PCV could have played a role in outbreak response, continued robust meningitis surveillance [29] , real-time specimen tracking [52] , high levels of laboratory confirmation [53] and pneumococcal serotyping in Burkina Faso will allow for monitoring and detection of any future pneumococcal meningitis clusters or outbreaks, as well as evaluation of a potential change from a 3 + 0 schedule to a 2 + 1 schedule and how that may impact pneumococcal meningitis dynamics in Burkina Faso.…”
Section: Discussionmentioning
confidence: 95%
“…One example of MenAfriNet country ownership is evident in the annual expansion of CBS from 2014 to 2018 despite no additional funding. Initially implemented in 76 districts across 4 countries, by 2018, Burkina Faso, Niger, Mali, Togo, and Chad expanded surveillance to 146 districts representing 48 million persons or 57% of the national population in these 5 high-risk countries [10]. MenAfriNet’s focus on country ownership has helped to achieve sustainable meningococcal surveillance in these countries.…”
mentioning
confidence: 99%
“…Five years after the establishment of MenAfriNet, this journal supplement provides an opportunity to describe the surveillance strategy, review performance, and highlight successes and challenges. Papers elsewhere in this supplement detail how MenAfriNet has improved surveillance performance and strengthened country capacity for laboratory confirmation [10–16], contributed to a greater understanding of current meningitis epidemiology in the meningitis belt [17, 18], and provided a platform for vaccine evaluation and research to inform existing and future bacterial meningitis vaccine policies [19–21]. This paper presents a look forward at priorities to control meningitis due to pathogens other than NmA, based on findings from MenAfriNet and other surveillance and research in the region, and at future directions for continuing MenAfriNet to ensure quality data are readily available to inform and evaluate future vaccination strategies for the meningitis belt in sub-Saharan Africa.…”
mentioning
confidence: 99%